Proses dan Faktor yang Memengaruhi Konversi Agama - Istikotimah Istikotimah; Siti Rokhimah (TSAQOFAH, 2026)
Religious conversion is a complex phenomenon that involves profound psychological, social, spiritual, and theological transformation. Although this phenomenon has been studied in various disciplines, discussions that integratively analyze the process, causal factors, and preventive strategies for the Muslim community still require conceptual strengthening. This study aims to analyze the process and factors that influence religious conversion and to formulate relevant preventive strategies for the Muslim community. This study used a qualitative approach with a literature review method through the synthesis of various academic sources, journals, and relevant texts. The results of the study show that religious conversion occurs through several stages, namely pre-conversion, searching, conversion experience as a turning point, and consolidation of belief. Internal factors that influence conversion include identity crisis, the search for meaning in life, profound spiritual experience, and theological awareness, while external factors include the social environment, interfaith marriage, exposure to digital media, economic conditions, and the influence of religious figures or communities. The case studies reviewed show diverse patterns of conversion according to individual backgrounds, ranging from rational intellectual searching to sudden spiritual shifts. The conclusion of this study affirms that religious conversion needs to be understood as a multidimensional process influenced by personal and social dynamics. The implications of this study include the importance of strengthening the Islamic creed, improving religious literacy, strengthening the role of the family as the main support system, empowering the Muslim community, utilizing digital technology for proactive and integrative da’wah, and developing sustainable and comprehensive Islamic education programs in building the theological resilience of the Muslim community in the contemporary era.